Komparasi Perkembangan Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), Dan Belanja Daerah Di Provinsi Kalimantan Tengah - Hendrik Suryadi; Alexandra Hukom (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to determine and analyze the comparative development of local revenue (PAD), general allocation funds (DAU) and regional expenditure in Central Kalimantan province. The variables used in this research are PAD, DAU and regional expenditure. This research uses a quantitative descriptive method using the One Way Anova analysis technique using SPSS software and obtains normality test results, homogeneity tests and one way Anova test results. The data used is secondary data sourced from the APBD posture, Central Kalimantan TKKD posture in the 2018-2022 period, from the internet, books and supporting journals in this research.